Mapeamento dos Recifes de Corais de Maracajaú/RN com o uso de Fotografias Aéreas de Pequeno Formato - GUIMARÃES DE LIMA, WILLIAMS DA SILVA; DO AMARAL, RICARDO FARIAS (Pesquisas em Geociências, 2001)
The Rio Grande do Norte State has many attractive natural resources. One of them is its large coast, which still contains many native beaches. Due the tropical weather, beaches of the Rio Grande do Norte can be visited by local people and tourist nearly all seasons of the year. The Maracajaú Coral Barrier, located at the shallow platform of Maxaranguape – RN, consists of a region that has turned into a touristic attraction in the last decades. The principal reason for the increasing in the touristic exploration of the region is the favorable conditions of temperature of water, transparence and the shallow depth of the region that surround the Maracajú Coral Barrier. Despite of supporting a large part of the local finances, the disorganized exploration of the touristic activities, specially at the adjacencies of the coral barrier, has produced several damages to the environment. The first step to a prudent exploration of the touristc activities, and other ways of exploration of the coral barrier, is the identification of the protected areas by developing of an appropriate cartographic basis that can be used to aid planning for the exploration of the environment. The development of maps began with the interpretation of small format aerial photographs (scale near of 1:5000), which were used to delimitate the geometry and morphologic features of the coral reef. The acquisition of small format photographs depends of climatic parameters, such as influence of tides, winds and the limpidity of the sky. Respecting these parameters, it is possible to investigate many features. In this work was identified sand waves, submerged and emerged coral reef bodies and submerged channels. Thus, it is necessary to improve the knowledge of the coral barriers of Maracajaú in the way to support more specific researches on this ecosystem, which can establish the potentialities of the area, allowing the exploration with minimized environmental damages.